Analisis Kinerja Petugas Apron Movement Control Dalam Meningkatkan Keselamatan Penerbangan di Apron Bandar Udara Abdul Rachman Saleh Malang - Kharisma Febry Wicaksono; Raden Fatchlul Hilal (LPPM Institut Nasional Laa Roiba Bogor, 2023)
Air transportation is currently the main choice for users who need time efficiency and convenience. AMC (Apron Movement Control) is the officer who is fully responsible for everything that happens on the Apron. Good AMC performance also affects the success of a flight. Given the very importance of airport operational activities which are activities that cannot be separated from the role of safety, work security and environmental protection activities. This study was conducted to find out how the performance of Apron Movement Control officers in improving flight safety on Apron at Abdul Rachman Saleh airport and what obstacles or obstacles the performance of Apron Movement Control officers were when carrying out their duties to improve flight safety at the airport. According to Sugiyono (2013) the research method is a scientific way to obtain data with certain goals and uses. This research method is a step that is owned and carried out by researchers in order to collect information or data and conduct investigations on the data that has been determined. In this study, researchers will use the type of qualitative research. According to Moleong (2011) states that qualitative research is research that intends to understand the phenomenon of what is experienced by the research subject. The results of the research on the performance of AMC (Apron Movement Control) at Abdul Rachman Saleh Airport, Malang, have been optimal in carrying out performance and are in accordance with the Regulation of the Director General of Civil Aviation Number: KP 21 of 2015 as well as those that have been determined by the company. Then the obstacles or obstacles faced by Apron Movement Control officers when carrying out tasks based on research and going into the field there were obstacles from inadequate and less helpful facilities in the performance process of Apron Movement Control employees as field implementers who always maintained safety in the Apron area. Apron Movement Control) Abdul Rachman Saleh Airport Malang is optimal in performing its performance and is in accordance with the Regulation of the Director General of Civil Aviation Number: KP 21 of 2015 as well as those determined by the company. However, there are facilities that are not appropriate and are not yet available with the provisions set by the government. Facilities and infrastructure at Malang Abdul Rachman Saleh Airport are not yet complete, and the lack of AMC personnel will cause problems from several factors. Keywords: Aviation Safety, Performance, Obstacles, Field Implementers, AMC (Apron Movement Control), Abdul Rachman Saleh Airport Malang